Spatial and temporal distribution of bottlenose dolphins, Tursiops truncatus, in the Madeira archipelago, NE Atlantic - Dinis, Ana (2016)
One of the first steps in understanding the relationships between populations and their habitats is to determine which areas they use with higher frequency. This study used systematic and non-systematic survey data from 2001-2002 and 2004-2012 to determine encounter rates and investigate temporal and spatial distribution of bottlenose dolphins around Madeira, Desertas and Porto Santo islands. A total 24,914 km of search effort was carried out and 199 sightings were recorded. Highest encounter rates were found off the east coast of Madeira and off Porto Santo. Moreover, higher encounter rates occurred over bathymetries ranging between 500-1,000 m during systematic surveys whereas in non systematic surveys relative high encounter rates were found in depths of 2,000-2,500m. Most dolphins were found to be distributed in depths <1,000m and at no more than 10 km offshore indicating a preference for shallower waters. Dolphins were sighted during the whole year and there were no significant differences in encounter rate between months. These results suggest the existence of preferential areas for this species based on static bathymetric features. The fact that the dolphins prefer inshore areas that are more exposed to anthropogenic activities should be taken into account when discussing bottlenose dolphin conservation measures in the Madeira archipelago.